2010
DOI: 10.1016/j.bmc.2010.08.053
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of radio-iodinated benzimidazoles as SPECT imaging agents for NR2B subtype of NMDA receptor

Abstract: In this study, the benzimidazole derivatives were synthesized and evaluated as imaging agents for the NR2B subype of NMDA receptor. Among these ligands, Although the brain uptake of these benzimidazole derivatives was too low to allow for in vivo SPECT imaging, these compounds might be useful scaffolds for the development of imaging probes specific for the NMDA receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The benzamidazole 2-{[4-(4-iodobenzyl)piperidin-1-yl]methyl}benzimidazol-5-ol showed high affinity for the GluN2B subunit, with a K i of 7 nM against [ 3 H]ifenprodil binding to rat cortical synaptic membranes [ 83 ]. When labelled with iodine-125 it showed excellent properties for autoradiography in vitro, but only moderate cerebral uptake in rats (0.5% ID/g at 30 min post injection).…”
Section: Glutamate Receptorsmentioning
confidence: 99%
“…The benzamidazole 2-{[4-(4-iodobenzyl)piperidin-1-yl]methyl}benzimidazol-5-ol showed high affinity for the GluN2B subunit, with a K i of 7 nM against [ 3 H]ifenprodil binding to rat cortical synaptic membranes [ 83 ]. When labelled with iodine-125 it showed excellent properties for autoradiography in vitro, but only moderate cerebral uptake in rats (0.5% ID/g at 30 min post injection).…”
Section: Glutamate Receptorsmentioning
confidence: 99%
“…In order to assess the binding characteristics of 11 C-benzyl amidines, we performed in vitro binding studies using rat-brain cryosection according to our previous work. 9 A typical in vitro binding autoradiogram of [ 11 C]CBA, [ 11 C]NBA, and [ 11 C]QBA of rat-brain sagittal sections showed high-radioactivity signals in the forebrain regions (the cerebral cortex and hippocampus), known to be GluN2B-rich regions, and lower signals in the cerebellum, a GluN2B-poor region (Figure 2A-C, respectively). These distribution patterns were consistent with the mRNA distribution of the GluN2B subunit.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…7 Although these ligands showed an extremely high in vitro selectivity for the GluN2B subunit, none of them showed specific binding in vivo. [8][9][10][11] Claiborne et al reported N-(benzyl) amidine derivatives as orally efficacious GluN2B-selective NMDAR antagonists. 12 In addition, Curtis et al have reported that cinnamyl and 2-naphthyl analogs of benzyl amidine (CBA and NBA) have high-GluN2B selectivity, extremely high-binding affinity (the K i values of CBA, and NBA for [ 3 H] ifenprodil binding are 0.7 nM and 1.3 nM, respectively), and methoxy groups, which can be labeled with carbon-11.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, treatment with nonradioactive 9 or the NR2B ligand, [(±)-( R * , S * )]-a-(4-hydroxyphenyl)- β -methyl-4-(phenylmethyl)-1-piperidine propanol (Ro 25–6981), caused 34% and 59% reduction in the brain/blood ratio of [ 125 I] 9 , respectively. This tracer may therefore show partially specific binding to the NR2B subunit in vivo [ 59 ]. Further structural modification of 9 may contribute to the development of more promising imaging probes for the NR2B subunit.…”
Section: Nmdarsmentioning
confidence: 99%